Longitudinal Analysis of GDP Growth and Islamic Finance Dynamic - sirat, Abdul Hadi; Daud, Nahu; ., Rusandry; Salleh, Maisyarah Stapah @; Possumah, Bayu Taufiq (Journal of Ecohumanism, 2024)
This research undertakes a longitudinal examination of the interplay between Gross Domestic Product (GDP) growth and the evolution of Islamic finance, with an emphasis on the total assets held by Islamic banking institutions. Utilizing time-series data from the years 2010 to 2023, this study applies a range of econometric methodologies, including Vector Autoregression (VAR) models, Granger causality assessments, and Seasonal-Trend Decomposition using LOESS (STL). The findings indicate that Islamic banking assets exert a significant short-term influence on GDP growth, with the VAR model elucidating essential dynamic interrelationships and Granger causality tests confirming predictive capacities at certain lags. Furthermore, the seasonal decomposition provides clarity on both long-term trends and short-term variations within the dataset. The results imply that while the total assets of Islamic banking have a marked short-term effect on GDP, other economic indicators such as export values, Islamic financing, and the Human Development Index exhibit minimal immediate influence. This study offers critical insights for policymakers and financial institutions, underscoring the necessity of incorporating Islamic finance metrics into economic planning and highlighting the imperative for further investigation into long-term effects and sector-specific ramifications.